2021
DOI: 10.1126/sciadv.abg3188
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the mechanism of human NPC1L1-mediated cholesterol uptake

Abstract: Niemann-Pick C1-like 1 (NPC1L1) protein plays a central role in the intestinal cholesterol absorption and is the target of a drug, ezetimibe, which inhibits NPC1L1 to reduce cholesterol absorption. Here, we present cryo–electron microscopy structures of human NPC1L1 in apo state, cholesterol-enriched state, and ezetimibe-bound state to reveal molecular details of NPC1L1-mediated cholesterol uptake and ezetimibe inhibition. Comparison of these structures reveals that the sterol-sensing domain (SSD) could respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“… 82 Recently, Hu et al found that SSD in NPC1L1 can respond to cholesterol concentrations by binding different amounts of cholesterol. 83 In addition, the effective cholesterol uptake by NPC1L1 depends on its dimerization. 84 Based on the crucial role of NPC1L1 in cholesterol uptake, ezetimibe has been developed and used clinically as an inhibitor of hypercholesterolemia, and other NPC1L1 inhibitors are being developed.…”
Section: Regulatory Mechanisms Of Cholesterol Homeostasismentioning
confidence: 99%
“… 82 Recently, Hu et al found that SSD in NPC1L1 can respond to cholesterol concentrations by binding different amounts of cholesterol. 83 In addition, the effective cholesterol uptake by NPC1L1 depends on its dimerization. 84 Based on the crucial role of NPC1L1 in cholesterol uptake, ezetimibe has been developed and used clinically as an inhibitor of hypercholesterolemia, and other NPC1L1 inhibitors are being developed.…”
Section: Regulatory Mechanisms Of Cholesterol Homeostasismentioning
confidence: 99%
“…As a homolog of NPC1, NPC1L1 likewise possesses a transmembrane domain with 13 cysteines and three major luminal structural domains in the extracellular area, the N-terminal domain (NTD), the middle domain (MLD), and the cysteine-rich domain (CTD). Thirteen molecules of membrane-embedded transmembrane helices (TM) make up the transmembrane domain (TMD) ( Hu et al, 2021 ). The SSD domain is widely distributed in several regulatory protein substructures that are closely related to cholesterol metabolisms, such as NPC1, sterol regulatory element-binding protein cleavage activating protein (SCAP), and hydroxymethyl glutaryl-CoA reductase (HMG-CoA reductase) ( Yang et al, 2012 ).…”
Section: Structure and Function Of Npc1l1mentioning
confidence: 99%
“…Huang et al studied the structure of NPC1L1 derived from Rattus . Miao Qinghu et al ( Hu et al, 2021 ) and Long et al (2021 ) studied the structure of human-derived NPC1L1. Their findings demonstrated a general similarity between the three-dimensional architecture of mouse and human NPC1L1.…”
Section: Structure and Function Of Npc1l1mentioning
confidence: 99%
“…PS, as well as cholesterol, are quickly uptaken by the enterocyte (Igel et al, 2003). Due to its structural similarity to cholesterol, PS can be uptaken by enterocytes through the Niemann-Pick C1-like 1 (NPC1L1) multi-pass transporter (Hu et al, 2021). Between these two types of molecules, plant sterol is better absorbed than stanol (Igel et al, 2003), suggesting that their chemical structure play an important role.…”
Section: Enterocyte Uptake and Blood Absorptionmentioning
confidence: 99%